Radiation and systemic immunotherapy for metastatic uveal melanoma: a clinical retrospective review - Tran, Danielle H.; Shanley, Ryan; Giubellino, Alessio; Tang, Peter H.; Koozekanani, Dara D.; Yuan, Jianling; Dusenbery, Kathryn; Domingo-Musibay, Evidio (Frontiers in Oncology, 2024)
Metastatic uveal melanoma (mUM) is a difficult to treat disease. The liver is the primary site of metastasis in most patients, though uveal melanoma spreads widely in advanced disease. The only FDA approved immunotherapy medication for metastatic uveal melanoma is the HLA-A02:01 restricted bispecific T cell engager drug, Tebentafusp. Checkpoint inhibitor strategies and combination approaches have been tried with some limited success. We describe our experience treating patients at the University of Minnesota. Patients were included if they had biopsy-confirmed mUM. Twenty-five (25) patients meeting the criteria were identified. Medical records were reviewed and data extracted for patient baseline characteristics and response to treatments. Median time to metastasis from the time of local therapy to the eye was 14.2 months (IQR; 9.3-22.0), and first site of metastasis was liver in 92% of patients. Two patients (8%) did not receive systemic therapy or radiation therapy for metastatic disease. Twenty-three (92%) patients received systemic therapy, 13 patients (52%) received ipilimumab-nivolumab as the first-line, while 4 patients (16%) received pembrolizumab. Landmark survival analysis by receipt of systemic therapy and radiation therapy treatments within 6 months of biopsy confirmed diagnosis is shown. Twenty patients (80%) received systemic therapy within 6 months of mUM diagnosis. Thirteen patients (52%) received liver directed radiation therapy within 6 months of mUM diagnosis. Within our cohort, there was no overall survival benefit for patients receiving treatment of metastatic disease within 6 months of mUM diagnosis, versus those electing later or no treatment at all. There was remarkable clinical activity of ipilimumab and nivolumab in a subset of patients with mUM, in agreement with prior studies, and metastatic PD-L1 positive tumors were associated with a prolonged survival.